A facile preparation of polyaniline/cellulose hydrogels for all-in-one flexible supercapacitor with remarkable enhanced performance. (1st October 2020) - Gong, Qiang; Li, Yueqin; Liu, Xiaohui; Xia, Zongbiao; Yang, Yong
Graphical abstract: Highlights: An easy handling method was designed to prepare a series of PANI/(β)CD-g-Cell CHPs. Grafting of β-CD to the surface of cellulose fibers enhances the adherence and flexibility of PANI/(β)CD-g-Cell CHPs. The PANI/(β)CD-g-Cell CHPs can be directly served as all-in-one supercapacitors. The all-in-one supercapacitors exhibit remarkable enhanced performances. This work provides a facile preparation of eco-friendly composites for energy storage. Abstract: In this paper, a series of conductive polymer hydrogels based on the β-cyclodextrin grafted cellulose hydrogels with nanostructured polyaniline embedding in three-dimensional networks have been developed. The obtained conductive hydrogels show high flexible and adequate adhesive behavior that endows easy fabrication of all-in-gel supercapacitors, in which the conductive hydrogels can be directly sandwiched between carbon cloths to fabricate extensive all-in-one supercapacitor devices without secondary packaging. The all-in-one supercapacitor delivers superior areal specific capacitance of 1003.50 m F/cm 2 without compromising rate capability, which is much higher than those previous reported hydrogels-based supercapacitors. Meanwhile, the supercapacitor exhibits maximum energy density of 89.20 μWh/cm 2 and high power density of 800.00 μW/cm 2, as well as reliable durability with capacitance retention of 90 % after 2000 consecutive charge-discharge cycles. Three all-in-one supercapacitors in series connection can drive a flash light-emitting diode, which conveys a potential application for eco-friendly energy storage devices.